The impact of nanoparticles on aerobic degradation of municipal solid waste - Guvenc, Senem Yazici; Alan, Burcu; Adar, Elanur; Bilgili, Mehmet Sinan (SAGE PUBLICATIONS LTD, 2017)
The amount of nanoparticles released from industrial and consumer products has increased rapidly in the last decade. These products may enter landfills directly or indirectly after the end of their useful life. In order to determine the impact of TiO2 and Ag nanoparticles on aerobic landfilling processes, municipal solid waste was loaded to three pilot-scale aerobic landfill bioreactors (80 cm diameter and 350 cm height) and exposed to TiO2 (AT) and Ag (AA) nanoparticles at total concentrations of 100 mg kg(-1) of solid waste. Aerobic landfill bioreactors were operated under the conditions about 0.03 L min(-1) kg(-1) aeration rate for 250 days, during which the leachate, solid waste, and gas characteristics were measured. The results indicate that there was no significant difference in the leachate characteristics, gas constituents, solid quality parameters, and temperature variations, which are the most important indicators of landfill operations, and overall aerobic degradation performance between the reactors containing TiO2 and Ag nanoparticles, and control (AC) reactor. The data also indicate that the pH levels, ionic strength, and the complex formation capacity of nanoparticles with Cl- ions can reduce the toxicity effects of nanoparticles on aerobic degradation processes. The results suggest that TiO2 and Ag nanoparticles at concentrations of 100 mg kg(-1) of solid waste do not have significant impacts on aerobic biological processes and waste management systems.
Keywords: Nanoparticles; municipal solid waste; aerobic landfill; bioreactors; leachate; TITANIUM-DIOXIDE NANOPARTICLES; BIOLOGICAL NITROGEN REMOVAL; SILVER NANOPARTICLES; ENGINEERED NANOMATERIALS; ENVIRONMENTAL EXPOSURE; LEACHATE RECIRCULATION; AGGREGATION KINETICS; IONIC-STRENGTH; LANDFILL; WATER; Engineering; Environmental Sciences & Ecology